A Study of the Metafunctions of Lombok Regional Slogans: Systemic Functional Linguistics Analysis - Syamsurrijal, Syamsurrijal; Arniati, Fitri (JOLLT Journal of Languages and Language Teaching, 2024)
Slogans are now an essential aspect of daily life, commonly encountered in both public businesses and industries such as soft drinks, food, fashion, cosmetics, and markets. While many slogans are written in the national language, numerous others are composed in local dialects. In Indonesia, every region has its own slogan in the local language. On the island of Lombok, there are four regions, and each has its own slogan in the local language, conveying a variety of messages to the inhabitants.Â  But numerous people from Lombok, especially the younger generation, are unable to understand the meaning and message conveyed through the slogans. As a result, this study is aimed at (1). An analysis of the metafunction conveyed by district slogans on Lombok Island, WNT Province, and (2) Determine the type of transitivity system process that is predominantly used in district slogans on Lombok Island, WNT Province. The study employed a descriptive qualitative and quantitative research design. The sample respondents were selected through purposive sampling and data was collected using survey, observation, and interview methods. Results indicate that the slogan encompasses ideational, interpersonal, and textual metafunctions, and also involves material, mental, relational, behavioural, and extension transitivity system processes. Quantitatively, the slogan employs 28 types of processes, with material processes making up the majority (27%), followed by relational processes (23%) and behavioural processes (19%). The slogan text does not contain any verbal processes. Participants related to the slogan text include human resources, goals, actors, sensing, phenomena, and behaviour.